Synchronous presentation of renal cell carcinoma and cervical cancer: a rare oncological challenge - Chadha, Saloni; Gupta, Sumedha; Kalwaniya, Dheer Singh; Chadha, Sudhir (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Cervical cancer is the fourth most common cancer among women globally, with a high incidence and mortality, particularly in developing countries. Renal cell carcinoma (RCC), though less common, comprises 2% of global cancer diagnoses. The synchronous occurrence of RCC and cervical cancer is extremely rare, with less than 5% of cervical cancer cases presenting with another primary malignancy. We report a case of a 47-year-old multiparous woman diagnosed with FIGO stage IIIB cervical cancer, who, during staging and evaluation, was incidentally found to have a synchronous renal cell carcinoma. During the course, imaging revealed a mass in the right kidney, confirmed to be RCC via biopsy. A multidisciplinary tumor board recommended surgical management for the RCC, and the patient underwent a right radical nephrectomy, which confirmed clear cell RCC. Postoperatively, the patient resumed treatment for cervical cancer with concurrent chemoradiation. This case highlights the importance of comprehensive diagnostic imaging in patients with pelvic malignancies to detect any coexisting primary tumors. Early identification and treatment of synchronous malignancies are critical for optimizing patient outcomes, and this case contributes valuable insight into the rare co-occurrence of RCC and cervical cancer.